The Directed ortho Metalation (DoM)–Cross-Coupling Connection: Synthesis of Polyfunctional Biaryls - Quesnelle, Claude A.; Snieckus, Victor (Synthesis, 2018)
A comparative evaluation of the combined directed ortho metalation (DoM)–Suzuki–Miyaura and DoM–Negishi cross-coupling reactions with aryl triflates for the synthesis of substituted biaryls is described. Both ortho-zinc and ortho-boron aryl directed metalation group (DMG = CON(i-Pr)2, OCONEt2, OMOM, NHBoc) substrates were evaluated. The superiority of the DoM–Negishi over the DoM–Suzuki–Miyaura reaction in operational convenience and mild reaction conditions is noted. Orthogonal Negishi and Suzuki–Miyaura with Corriu–Kumada reactions for the synthesis of a teraryl derivative is also reported.
Keywords: Suzuki–Miyaura coupling; Negishi coupling; cross-coupling; directed ortho metalation